Essential Google Cloud Training: Deploy, Analyze, and Secure Your Cloud Environment. - Sullivan, Dan; , Pearson (linkedin.com, 2024)
Learn the skills you need to deploy infrastructure, develop applications, manage networks, and use specialized services like serverless data warehousing on the Google Cloud Platform.